Study on Assessment Method of Satellite Damaged by Space Debris. Issue 1 (May 2019) - Gu, Hongping; Shi, Yijian; Cheng, Chun; Wang, Quan; Fu, Jie; Sui, Hongxia; Xu, Tongkun
Abstract: The damage assessment model of space debris was established to satellite, included the description of space debris distribution field, the analysis of function and structure of satellite components, the rendezvous analysis between space debris and satellite, the damage criterion and so on. NASA ORDEM model and Shot-line method were used to describe the probability distribution field of millimeter and centimeter debris in space. The equivalent model of satellite was established by energy conservation principle and basic body method. The failure probability of satellite system was calculated under the impact of space debris. Establishing the vulnerability analysis method of satellite target is great significance to the risk assessment of space debris impacting satellite, and provides reference for the optimization design of satellite protection structure.